Bison as Engineers of the Prairie Waterscape - Heidi Mehl (Symphony in the Flint Hills, 2018)
Introduction: Western science has only relatively recently begun to appreciate many of the far-reaching and cascading impacts that the complete removal of a species can have on an ecosystem. For example, recent research has shown strong linkages between the reintroduction of wolves and elk browsing behaviors, which, in turn, have affected willow and cottonwood recruitment, beaver populations, and stream form and function in Yellowstone National Park. Similarly, the influence of American bison (Bos bison) as prairie ecosystem engineers extends not only to healthy grassland maintenance, but also to healthy prairie streams and aquatic ecosystems.